SGB parent members' and other parents' attitudes towards inclusion and exclusion in primary schools - Kern, Anwynne C. (My University, 2022)
In South Africa the changes in education, emerging from several government documents, resulted in the implementation of inclusive education through the Education White Paper 6. Since then, research into the role of stakeholders in the implementation of inclusion in South Africa has largely focused on teachers. However, parents are also instrumental in the successful implementation of inclusion, particularly in their role as members of School governing bodies. Consequently, the aim of this study was to explore parents’ perception of inclusion and exclusion from a Capability perspective in the context of South African primary schools. In addition, given the governance roles of parents assigned to them through the South African Schools Act, an understanding of the perception of parent governors, as well as those not part of school governing bodies was sought. The study employed a two-phase sequential explanatory mixed method design. Quantitative data were generated from a sample of 901 parents of primary school aged children, drawn from seven primary schools in the Gauteng Province, using a self-developed survey. The qualitative data were generated through semi-structured interviews with 22 parents. The survey data were analysed employing descriptive statistics using frequency analysis. The interview transcripts and survey open-ended questions were analysed using thematic analysis. The analysis indicates parents have an understanding of inclusion centred on person characteristics. Parents considered the factors of disability, language, socio-economic status, behaviour and learning ability in expressing their understanding of inclusion and exclusion. Parents also demonstrated an understanding of formal and epistemological access regarding enrolment and what happens to children once they are enrolled at school. Parents’ consideration of epistemological access also resulted in an expression of the perceived positive and negative impact of inclusion and exclusion. The findings indicate despite parents’ support of the idea of inclusion they have concerns regarding its implementation and its impact on the quality of education their child would receive. An analysis of the results using the Capability approach and the Bio-ecological theory demonstrated gaps in its usage. These gaps were addressed through a conceptual framework integrating concepts drawn from the Bio Ecological theory and Capability approach. In the conceptual framework I argue that understanding what functioning is valued, and how individuals come to value that specific functioning, through the integration of concepts drawn from both the Capability approach and the Bio-Ecological framework, is important in understanding parents support for inclusion.
A thesis submitted in fulfilment of the requirements for the Doctor of Philosophy in Psychology to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2022